An Empirical Study of Historical Patterns in Musical Rhythm: Analysis of German & Italian Classical Music Using the nPVI Equation. - Patel, Aniruddh D.; Daniele, Joseph R. (Tufts University. Tisch Library., 2016)
This paper introduces a new approach for the historical study of musical rhythm based on an empirical measure of rhythm known as the nPVI ('normalized pairwise variability index') The nPVI is an equation that measures the degree of durational contrast between successive events in a sequence. While the nPVI is increasingly used for comparative studies of rhythm in music and language, we show that it can also be used for historical research. A historical analysis of musical nPVI values from German/Austrian and Italian instrumental classical music between ∼1600-1900 reveals different patterns in the two cultures: German/Austrian music shows a steady increase in nPVI values over this period, while Italian music shows no salient increase. These patterns are discussed in light of the idea (from historical musicology) that the influence of Italian music on German music began to wane in the second half of the 1700s due to a rise of musical nationalism in Germany. The nPVI data prove to be consistent with this idea, illustrating how nPVI analysis can reveal patterns that enrich and inform historical research.